Peran Kyai Dalam Pembentukan Karakter Disiplin Santri Pondok Pesantren Mambaus Sholihin Roudlotul Muta’allimin - Ach. Khusnan; Pristiwiyanto; Aan Abdurrahman Aflikh (Jurnal Pendidikan Agama Islam Miazhar, 2025)
This research explains the analysis of the role of kyai in forming the disciplined character of santri. The character of santri is the behavior that santri have from birth, but the disciplined character of santri grows from the upbringing of the parents or guardians of previous santri who then continued their education at the Islamic boarding school. where the students' education will be guided directly by the kyai and assisted by the ustadz-ustadzah at the Mambaus Sholihin Roudlotul Muta'allimin Islamic boarding school, Suci village, Manyar Gresik sub-district. When under the guidance of kyai and ustadz-ustadzah there will be further positive changes in the disciplined character of these students, where characters who are not good or have not been disciplined will eventually change over time in pursuing education at the Islamic boarding school. This type of research is descriptive qualitative research by selecting students at the Mambaus Sholihin Roudlotul Muta'allimin Islamic boarding school, Suci village, Manyar Gresik sub-district as samples and three informants who are considered to have knowledge and information regarding the problems studied, namely the Role of Kyai in Forming Disciplined Character of Santri at Mambaus Islamic Boarding School. Sholihin Roudhotul Muta'allimin Suci Village, Manyar District, Gresik Regency. The data collection techniques used are observation, interviews and documentation. To check the validity of the data in this study, a credibility test was used. The results of this research show quite good results regarding the Role of Kyai in Forming the Disciplined Character of Santri at the Mambaus Sholihin Roudlotul Muta'allimin Islamic Boarding School by interviewing informants as seen from the interview indicators, namely the role of the kyai in forming the disciplined character of the santri and the disciplinary character of the santri at the Mambaus Sholihin Roudlotul Islamic boarding school. muta'allimin Suci Village, Manyar District, Gresik Regency.